[OP.3D.06] RELATIONSHIP BETWEEN DIFFERENT POPULATIONS OF CIRCULATING T LYMPHOCYTES AND MICROVASCULAR OXIDATIVE STRESS. (September 2016) - De Ciuceis, C.; Rossini, C.; Airò, P.; Scarsi, M.; Piantoni, S.; Gavazzi, A.; Solaini, L.; Porteri, E.; Petroboni, B.; Rosei, C. Agabiti; Tincani, A.; Rosei, E. Agabiti; et al.
Abstract : Objective: Both innate and adaptive immune systems may contribute to the pathogenesis of cardiovascular disease and vascular remodeling through inflammation and oxidative stress. Particularly, the balance between Th1 effector lymphocytes (producing interferon-γ) and T regulatory (Treg) lymphocytes, which elicit an anti-inflammatory activity, may be crucial for blood pressure elevation and organ damage development, at least in experimental models. In particular, Tregs have been previously demonstrated to inversely correlate with subcutaneous small resistance artery media to lumen ratio (M/L) and retinal arteriole wall to lumen ratio (W/L) (unpublished data). Therefore, we evaluate the possible relationship between Th1 or Treg lymphocytes and microvascular oxidative stress. Design and method: We enrolled 11 normotensive subjects and 4 hypertensive patients undergoing an election surgical intervention. No sign of local or systemic inflammation was present in any subjects or patients. All patients underwent a biopsy of subcutaneous fat during surgery. A peripheral blood sample was obtained before surgery for assessment of T lymphocyte populations. Lymphocyte phenotype was evaluated by flow cytometry after 5 hour in vitro activation in order to assess Th1 lymphocytes. Superoxide anion production, as index of oxidative stress, was evaluated in the bioptic tissue by florescent dye dihydroethidium and quantified using an image analyzer. Results: Results are summarized in the Table (RTE: recent thymus emigrant; EM: effector memory). Figure. No caption available. A significant positive correlation was observed between Th1 lymphocytes and superoxide anion production in subcutaneous microvessels. Additionally, a significant inverse correlation was observed between microvascular free radical production and Total Treg, RTE and EM Tregs. Conclusions: Our data suggest that Treg lymphocytes may be protective against microvascular damage, probably because of their anti-oxidant properties confirming an involvement of adaptive immune system on microvascular damage.